2017
DOI: 10.1016/j.jjcc.2016.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac contractility modulation in heart failure patients: Randomized comparison of signal delivery through one vs. two ventricular leads

Abstract: The efficacy and safety of CCM in this study were similar when the signal was delivered through either one or two ventricular leads. These results support the potential use of a single ventricular lead for delivery of CCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
(32 reference statements)
2
9
0
2
Order By: Relevance
“…21 In a recent study, it was demonstrated that efficacy and safety of CCM were similar when the signal was delivered through either 1 or 2 ventricular leads. 22 These results support the potential future use of a single ventricular lead for delivery of CCM, further reducing device implantation-associated risk.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…21 In a recent study, it was demonstrated that efficacy and safety of CCM were similar when the signal was delivered through either 1 or 2 ventricular leads. 22 These results support the potential future use of a single ventricular lead for delivery of CCM, further reducing device implantation-associated risk.…”
Section: Discussionsupporting
confidence: 60%
“…The new mode also allows the delivery of CCM therapy in patients with permanent atrial fibrillation, which was considered a contraindication for the prior‐generation Optimizer device . In a recent study, it was demonstrated that efficacy and safety of CCM were similar when the signal was delivered through either 1 or 2 ventricular leads . These results support the potential future use of a single ventricular lead for delivery of CCM, further reducing device implantation–associated risk.…”
Section: Discussionmentioning
confidence: 88%
“…Future changes can be anticipated in the refinement of this technology. A small randomized control trial of 48 patients found that the efficacy and safety of CCM was similar when the signal was delivered through a single ventricular lead rather than dual ventricular leads [49]. Thus, future models will likely consist of a single ventricular lead.…”
Section: Future Perspectivementioning
confidence: 99%
“…Параметрами, независимо связанными с наступлением вторичной ККТ в течение 2 лет у пациентов, получающих терапию МСС, стал NTproBNP. Интересно, что отключение одного из электродов не повлияло на смертность и госпитализации, что согласуется с данными исследования Röger S, et al (2017), где стимуляция только одним электродом по сравнению с двухэлектродной стимуляцией зоны межжелудочковой перегородки не оказывала существенного воздействия на ФК ХСН, пиковое потребление кислорода и смертность в течение 6 мес. МСС терапии [14].…”
Section: Discussionunclassified